DICHOTIC RESPONSE PROPERTIES OF DURATION-TUNED NEURONS IN THE BAT - Dubovan, Daniel (My University, 2018)
Inhibitory synaptic inputs are necessary for the formation of duration tuned neurons (DTNs) in the mammalian inferior colliculus (IC). These neurons may help to differentiate the temporal aspects of sound. Much more is known about the characteristics of the monaural contralateral inputs that create DTNs compared to their ipsilateral inputs. The current study used paired-tone stimulation and single-unit extracellular recording to measure the frequency tuning of the neural inhibition evoked from stimulating the ipsilateral ear in the big brown bat (Eptesicus fuscus). The stimulus consisted of a short duration, excitatory probe tone set to the cell’s best duration (BD) and varying in onset time relative to a longer duration, non-excitatory (NE) suppression tone. In the monotic condition, both tones were presented to the contralateral ear and when they were close in time the NE tone always suppressed spikes evoked by the BD tone. In the dichotic condition, the BD tone was presented to the contralateral ear and the NE tone was presented to the ipsilateral ear (i.e. the same side as the IC hemisphere being recorded), but now the NE tone suppressed BD tone evoked spiking in a smaller proportion of cells. Frequency tuning, latency, and duration of the ipsilaterally-evoked inhibition was investigated by varying the NE tone frequency both within and outside a cell’s 50% excitatory bandwidth (eBW) that was measured by stimulating the contralateral ear only. The inhibition evoked contralaterally differed from that evoked ipsilaterally in three respects: 1) the contralateral inhibition led contralateral excitation whereas ipsilateral inhibition usually lagged contralateral excitation; 2) the duration of contralateral inhibition persisted as long or longer than the duration of the NE tone, whereas the duration of ipsilateral inhibition was usually shorter than the NE tone duration; and 3) the bandwidth of contralateral inhibition was broader than the cell’s eBW, while the bandwidth of ipsilateral inhibition was more variable compared to the eBW. There were some similarities between the contralateral and ipsilateral evoked inhibitions: 1) the best inhibitory frequency (BIF) and best excitatory frequency (BEF) matched in both conditions; 2) the duration of inhibition decreased as the NE tone frequency departed from the cell’s BEF; and 3) the onset of inhibition was frequency independent both in the monotic and dichotic conditions. These data suggest the temporal selectivity of midbrain DTNs is created by monaural auditory inputs, with ipsilateral inputs playing a lesser role in shaping the cell’s duration selectivity. Ipsilateral inhibition, when present, may play a role in shaping the response of DTNs to sounds presented in different locations rather than creating duration-selectivity like the monaural pathway.
Response Properties of Ipsilateral Inputs in Duration Tuned Neurons